Polycyclic compound and preparation method, use, electrolyte and battery thereof
By preparing high-purity polycyclic compounds as electrolyte additives, the problem of difficulty in controlling the content of free chlorine ions in the electrolyte is solved, and the electrochemical performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202410757961.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-13
AI Technical Summary
The prior art is difficult to effectively reduce the content of free chloride ions in the electrolyte, resulting in poor battery performance, corrosion of the positive electrode foil and dissolution of transition metal ions.
By preparing a polycyclic compound with a content of ≥99wt% and a total content of chlorine-containing organic matter of ≤300ppm, it is used as an electrolyte additive to improve the electrochemical performance of the battery.
It effectively reduces the content of free chloride ions in the electrolyte, reduces the risk of corrosion of the positive electrode foil and the dissolution of transition metal ions, and improves the cycle stability and electrochemical performance of the battery.
Smart Images

Figure CN118307530B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of batteries, and specifically, relates to polycyclic compounds and preparation methods, uses, electrolytes and batteries thereof. Background Art
[0002] With the rapid development of electronic equipment, electric vehicles, smart homes, power tools, smart transportation and other markets, the demand for batteries is also increasing. Taking lithium-ion batteries as an example, they are widely used in consumer electronics, energy storage and power batteries, smart homes and other fields because of their advantages such as high specific energy, long cycle life and low self-discharge. Usually, the battery includes a positive electrode, a negative electrode, a separator and an electrolyte. The electrolyte usually includes a solvent, an electrolyte lithium salt and an electrolyte additive. The performance of the battery can be improved by adding electrolyte additives to the electrolyte. Among them, the content of free chloride ions in the electrolyte is strictly controlled, generally required to be less than 5ppm. Free chloride ions are not only easy to induce corrosion of the positive electrode foil (such as aluminum foil), but also easy to cause the dissolution of transition metal ions in the positive electrode of the battery, affecting the electrochemical performance of the battery. In the electrolyte, chloride ions mainly come from lithium salts and various additives. Therefore, the selection of suitable additives has an important influence on the electrochemical performance of the battery. Summary of the invention
[0003] The present application aims to solve one of the related technical problems to a certain extent.
[0004] The technical solution of this application is completed by the inventor based on the following findings:
[0005] The free chloride ions in the electrolyte have a great influence on the battery performance. At present, most of the technicians in this field are committed to reducing the content of free chloride ions in the electrolyte, but in actual situations, the performance is still not optimal. The inventors of the present application found that the conventional method of detecting chloride ions in the electrolyte cannot detect certain chlorine-containing organic substances with specific structures, because these chlorine-containing organic substances with specific structures are difficult to dechlorinate under the existing test conditions, so that they exist in the form of chloride ions. Therefore, the existing test methods cannot detect them, causing the technicians in this field to ignore the control of the content of chlorine-containing organic substances. It is precisely these chlorine-containing compounds with specific structures that have a significant negative impact on the performance of the electrolyte. The reason may be that: the battery cell usually contains trace amounts of water and some residual alkaline substances. If there are too many chlorine-containing organic impurities in the electrolyte additives, after applying them to the electrolyte, during the operation of the battery, under the conditions of high temperature and high pressure, especially under the action of residual alkaline substances, the chlorine-containing organic impurities are prone to hydrolysis, resulting in an increase in the free chlorine content in the electrolyte, which is not only easy to induce corrosion of the positive electrode foil (such as aluminum foil), but also easy to cause the dissolution of transition metal ions in the positive electrode of the battery, which will not only lead to a decrease in the structural stability of the positive electrode active material, but also the dissolved transition metal ions are easy to deposit on the surface of the negative electrode, resulting in the continuous decomposition and regeneration of the SEI film, and the continuous consumption of active lithium. The dissolution of transition metal ions, the decomposition and regeneration of the SEI film will promote the decomposition of the electrolyte, which is easy to cause battery capacity decay, increased polarization due to SEI film thickening or electrolyte consumption and by-products blocking the lithium insertion and extraction channels, and increased short circuit risks. The impact on low-temperature discharge, high-temperature storage and cycle performance is relatively large. Even under the requirements of relevant standards, the moisture content in the battery cell is controlled, but the requirements for free chloride ions in the standards are more stringent than those for moisture. That is to say, even if the moisture content in the battery cell is not much, but under the action of moisture exceeding the free chloride ion standard, once the chlorine-containing organic matter is hydrolyzed, it will easily make the free chloride ion content exceed the standard, thereby deteriorating the performance.
[0006] In addition, as an important component of lithium secondary batteries, electrolyte has an important influence on the comprehensive performance of batteries. Additives are an important component of electrolytes, and suitable additives can significantly improve the electrochemical performance of batteries. The inventors also found that the compound shown in Formula I is used as an additive in lithium battery electrolytes, which has a good improvement effect on the electrochemical performance of batteries. However, the use of existing synthesis processes to prepare compounds shown in Formula I generally has problems such as high impurity content of target products, low synthesis efficiency and yield. For example, there is currently a method of transesterifying hexavalent alcohols and carbonates under catalyst catalysis, and then adding sulfonyl chloride to recrystallize to obtain the target product, but the selectivity of this method is poor, it is relatively difficult to obtain a single target product, the target product yield is low, and the generated impurities are more. In addition, the use of sulfonyl chloride as a reaction raw material is also prone to the presence of more chlorine-containing organic impurities in the synthesized target product.
[0007] In view of this, the first object of the present application is to provide a polycyclic sulfate product, which has high product purity and a chlorine-containing organic matter content of less than 300 ppm, thereby being able to reduce the impact of chlorine-containing organic matter on battery performance while improving battery performance.
[0008] In the first aspect of the present application, a polycyclic compound is provided, comprising: a compound represented by formula I and a chlorine-containing organic matter, wherein the content of the compound represented by formula I is ≥99wt% and the total content of the chlorine-containing organic matter is ≤300ppm based on the mass of the polycyclic compound.
[0009] ,
[0010] In formula I, R1 and R2 are independently any one of H, F, alkyl and fluoroalkyl.
[0011] The above-mentioned polycyclic compound of the present application has the following beneficial effects: the compound shown in Formula I can be used as an additive in the electrolyte, which can improve the electrochemical performance of the battery. Specifically, it is not only conducive to forming a dense CEI film at the positive electrode and a dense SEI film at the negative electrode, but also forms a small amount of inorganic salts in the CEI film formed by decomposition of the positive electrode (taking lithium batteries as an example, the inorganic salts include Li2SO4 and / or Li2O), which improves the rigidity and flexibility of the positive electrode interface layer, inhibits the decomposition of the electrolyte, and improves the stability of the positive electrode interface film. In addition, the CEI film formed by the compound shown in Formula I can also reduce the electrochemical impedance of the positive electrode and accelerate the active ions (such as Li +) transmission rate, and at the same time help to form a more stable electrode-electrolyte interface, reduce the internal resistance and interface reaction of the battery, and play a role in protecting the positive electrode. In addition, it can also inhibit the dissolution of transition metal ions in the active material of the positive electrode plate, reduce the cycle capacity attenuation of the battery, and improve the cycle stability; furthermore, the compound shown in Formula I will generate lithium carbonate in the SEI film formed at the negative electrode, and lithium carbonate helps to improve the film formation uniformity and stability of the SEI film. In addition, the compound shown in Formula I is easy to obtain electrons and be reduced to cause the SO single bond to break, and the three O atoms in O, S=O and S=O on another cyclic sulfate group in the transition state formed after the break can form a claw-type space structure, which is easy to capture metal ions to form a cage complex, thereby stabilizing the already dissolved transition metal, reducing the catalytic decomposition side reaction of the transition metal on the SEI film, and inhibiting the negative impact caused by the deposition of the transition metal in the form of a single substance after the negative electrode is reduced; furthermore, the compound shown in Formula I has a low impedance, which is also beneficial to reducing the battery impedance. However, the conventional synthesis process of the compound shown in Formula I inevitably contains impurities, and it is difficult to obtain a product with high purity and low impurity content. In particular, the existing synthesis method using sulfonyl chloride as a reaction raw material generally contains a large number of chlorine-containing organic impurities, and the chlorine-containing organic impurities are easily hydrolyzed, resulting in an increase in the free chlorine content in the electrolyte, which not only easily leads to corrosion of the positive electrode foil, but also easily leads to the dissolution of transition metal ions in the active material of the positive electrode sheet, reducing the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery. In the present application, by using a polycyclic compound having a content of the compound shown in formula I of ≥99wt% and a total content of chlorine-containing organic matter of ≤300ppm as an additive in the electrolyte, the increase in the free chlorine content in the electrolyte caused by the introduction of the additive can be effectively reduced, thereby reducing the risk of corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet caused by the increase in the free chlorine content of the electrolyte. As a result, the problem of a decrease in the improvement effect of the compound shown in formula I on the electrochemical performance of the battery due to the presence of chlorine-containing organic impurities can be effectively improved, thereby improving the improvement effect of the polycyclic compound on the electrochemical performance of the battery.
[0012] In some embodiments, the chlorine-containing organic compound includes chlorine-containing organic compound without cyclic sulfate groups and cyclic carbonate groups, chlorine-containing organic compound containing only cyclic carbonate groups, chlorine-containing organic compound containing only cyclic sulfate groups, and chlorine-containing organic compound containing 1 to 2 cyclic carbonate groups and 1 cyclic sulfate group.
[0013] In some embodiments, R1 and R2 are independently any one of H, F, and fluoromethyl.
[0014] In some embodiments, based on the mass of the polycyclic compound, the total content of the chlorine-containing organic matter is ≤100 ppm, thereby further improving the problem that the improvement effect of the compound represented by Formula I on the electrochemical performance of the battery is reduced due to the presence of chlorine-containing organic impurities.
[0015] Based on the mass of the polycyclic compound, the content of the compound represented by Formula I is greater than 99.9wt%, thereby further improving the effect of the polycyclic compound on the electrochemical performance of the battery.
[0016] In some embodiments, the chlorine-containing organic compound includes , , One or more of .
[0017] In some embodiments, the polycyclic compound further comprises other organic matter, and the other organic matter is selected from one or more of the following six compounds: , , , , , .
[0018] In some embodiments, the compound represented by Formula I comprises: The compound has good stability, which is conducive to further improving the improvement effect of the polycyclic compound on the electrochemical performance of the battery.
[0019] In some embodiments, based on the mass of the polycyclic compound, the total content of the other organic matter is ≤1000 ppm, and optionally ≤200 ppm. This can further improve the problem of reduced improvement effect of the compound represented by Formula I on the electrochemical performance of the battery due to impurities.
[0020] In some embodiments, based on the mass of the polycyclic compound, , , The total content of is ≤50ppm. This can further improve the problem that the improvement effect of the compound represented by formula I on the electrochemical performance of the battery is reduced due to chlorine-containing organic impurities.
[0021] Based on the same inventive concept as the first aspect of the present application, it is expected to obtain a polycyclic compound product with a chlorine-containing organic matter content of ≤300ppm and a compound purity of ≥99wt% as shown in Formula I. Based on this purpose, a method for preparing polycyclic compounds in the second aspect of the present application was developed.
[0022] In a second aspect of the present application, a method for preparing a polycyclic compound is provided, comprising:
[0023] (1) mixing a hexahydric alcohol, a monohydric alcohol, a carbonate and an alkaline catalyst, and conducting an ester exchange reaction at a temperature of 65 to 100° C. and under a pressure controlled to be less than 2.5 MPa for 0.5 to 6 hours to obtain compound 1;
[0024] (2) dissolving the compound 1 in a solvent and reacting the mixture with thionyl chloride to obtain a compound 2;
[0025] (3) reacting the compound 2 with an oxidant to obtain a compound represented by formula I,
[0026] Wherein, the structural formulas of the hexahydric alcohol, the compound 1, and the compound 2 are respectively:
[0027] , , , R1 and R2 are independently any one of H, F, Cl, alkyl, and fluoroalkyl.
[0028] The above-mentioned method for preparing polycyclic compounds in the present application has the following beneficial effects: in the ester exchange reaction, the reaction activity of the hydroxyl groups at the terminal positions (1 and 6) of the hexamethylene alcohol is suppressed by using a monohydric alcohol and controlling the pressure to be less than 2.5 MPa, and then the reaction temperature is raised to 65-100°C, which is higher than the boiling point of the monohydric alcohol (methanol has the lowest boiling point of 65°C among the monohydric alcohols used in the present application), through the action of pressure, so as to increase the reaction activity of the hydroxyl groups at the middle positions (2, 3, 4, and 5) of the hexamethylene alcohol, so that the activity of the hydroxyl groups at the middle positions of the hexamethylene alcohol is much higher than that of the hydroxyl groups at the terminal positions. At the same time, under the conditions of heating and pressurization, compared with the products generated by the reaction of the hydroxyl groups at the 2nd and 3rd positions and the products generated by the reaction of the hydroxyl groups at the 4th and 5th positions, the products generated by the reaction of the hydroxyl groups at the 3rd and 4th positions (i.e., compound 1) have good symmetry and better stability. Therefore, under this condition, the selectivity for compound 1 and the conversion efficiency of compound 1 in the ester exchange reaction can be improved, and the intermediate product with compound 1 can be obtained with high conversion rate and high selectivity. Therefore, on the one hand, the residual hexamethylene alcohol content in the ester exchange reaction product can be effectively reduced, and on the other hand, the impurities can be reduced. , content, thereby helping to reduce the impurities that may be generated by the residual hexahydric alcohol or impurities participating in subsequent condensation reactions and oxidation reactions. , , , , , content. In addition, no additional organic solvent is used in the transesterification reaction of the present application, and carbonate and monohydric alcohol are both reactants and solvents, which is not only environmentally friendly but also easy to operate. In summary, the method not only has high selectivity and high conversion rate for the compound shown in Formula I, but also has low impurity content, which can effectively improve the problems of low reaction conversion rate, complicated reaction steps, more impurity generation and inconvenience for industrial production of the compound shown in Formula I during synthesis, and is also conducive to obtaining a target product with a content of chlorine-containing organic matter ≤300ppm and a purity of ≥99wt% of the compound shown in Formula I. The target product shown in the obtained Formula I is used in the electrolyte to effectively reduce the increase in the free chlorine content in the electrolyte, thereby reducing the risk of electrolyte corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet due to the increase in the free chlorine content. Thus, the problem of the decrease in the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery due to the presence of chlorine-containing organic impurities can be effectively improved, and the improvement effect of the obtained polycyclic compound on the electrochemical performance of the battery can be improved.
[0029] In the present application, since monohydric alcohol is used as the reaction raw material, it is limited by the boiling point of the monohydric alcohol (methanol has the lowest boiling point of 65°C among the monohydric alcohols used in the present application). Therefore, under normal pressure or negative pressure conditions, in the reaction system of the present application, the monohydric alcohol will evaporate and reflux when the temperature reaches its boiling point. During the reflux process, the solution temperature and the steam temperature will continuously adjust to each other and eventually reach a dynamic equilibrium. The inventors found that under this dynamic equilibrium, the temperature of the reaction system will stabilize at around the boiling point of the monohydric alcohol, making it difficult to increase the temperature of the reaction system, thereby limiting the reaction rate. The pressurization method of the present application can not only cooperate with the monohydric alcohol to improve the selectivity of the reaction, but also increase the boiling point of the monohydric alcohol, so that the reaction temperature can also be appropriately increased, thereby ultimately increasing the reaction rate.
[0030] In some embodiments, the temperature of the transesterification reaction is 70-90°C, the pressure is 0.5-2.2 MPa, and the time is 0.5-6 h; more preferably, the temperature of the transesterification reaction is 75-85°C, and the pressure is 1-2 MPa. In this way, a high raw material conversion rate and a suitable transesterification reaction rate can be taken into account, thereby obtaining compound 1 with high selectivity and yield and low impurity content.
[0031] In some embodiments, the molar ratio of the carbonate to the hexahydric alcohol is 3: 1 to 5: 1. This is beneficial for obtaining a suitable transesterification reaction rate and a high conversion rate, and is also beneficial for reducing the impurity content in the final product.
[0032] In the present application, the monohydric alcohol is used as a solvent on the one hand, and its addition amount is generally sufficient to completely dissolve the raw materials mannitol and carbonate. Under normal circumstances, the molar ratio of the monohydric alcohol to the hexahydric alcohol is greater than or equal to 10 to meet the dissolution requirements. The prior art mentions that in order to dissolve the raw materials, it does not matter if the solvent methanol is added excessively, but in fact, the inventors have found that the content of the monohydric alcohol also affects the selectivity of the transesterification reaction. If the content of the monohydric alcohol is too high (the molar ratio of the monohydric alcohol to the hexahydric alcohol is greater than 20:1), the selectivity of the transesterification reaction will be reduced to a certain extent. Based on this, in some embodiments, the molar ratio of the monohydric alcohol to the hexahydric alcohol is 10:1~20:1, preferably 12:1~18:1, and more preferably 14:1~16:1. This is conducive to obtaining a suitable transesterification reaction rate and a high conversion rate, and is also conducive to reducing the impurity content in the final product.
[0033] In some embodiments, based on the mass of the hexavalent alcohol, the amount of the alkaline catalyst is 0.01-5wt%, optionally 0.02-0.5wt%, and more preferably 0.02-0.1wt%. This is conducive to the smooth progress of the transesterification reaction and can also reduce the risk of increasing the amount of thionyl chloride used in the subsequent condensation reaction due to excessive use of the alkaline catalyst and generating more sulfur dioxide.
[0034] In some embodiments, the hexavalent alcohol includes one or more of mannitol, sorbitol, and galactitol.
[0035] In some embodiments, the carbonate includes one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and diphenyl carbonate.
[0036] In some embodiments, the monohydric alcohol includes one or more of methanol, ethanol, propanol, isopropanol, butanol, and tert-butanol.
[0037] In some embodiments, the alkaline catalyst includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, triethylamine, and pyridine.
[0038] In some embodiments, after the transesterification reaction is completed, the process further comprises: decompression treatment to remove low-boiling point components, thereby further improving the purity of the compound represented by Formula I and reducing the impurity content.
[0039] In some embodiments, in step (2), after the condensation reaction is completed, the step further includes: reflux deacidification treatment, thereby reducing the residual HCl generated by the condensation reaction.
[0040] In some embodiments, in step (2), the temperature of the reflux deacidification treatment is 40-80° C., and / or the time of the reflux deacidification treatment is 10-50 min. Meeting the reflux deacidification treatment conditions is conducive to further reducing the residual HCl generated by the esterification reaction.
[0041] In some embodiments, in step (2), after dissolving compound 1 in a solvent, thionyl chloride is added dropwise to carry out the condensation reaction. This can better inhibit impurities. Generation of.
[0042] In some embodiments, in step (2), the temperature of the condensation reaction is 20-100° C. This can better balance the reaction efficiency and the purity of the final product.
[0043] In some embodiments, in step (2), the molar ratio of the compound 1 to the thionyl chloride is 1:(2-3), and the thionyl chloride is added for 0.5-2 hours. This can take into account the reaction rate, improve the purity of the compound 2 and the final product, and reduce the impurity content.
[0044] In some embodiments, in step (2), the solvent includes one or more of an ether solvent, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, and an ester solvent.
[0045] In some embodiments, in step (3), the oxidant is provided in the form of an aqueous solution, and after reacting the compound 2 with the oxidant, the step further includes: heating the reaction product to remove moisture.
[0046] In the third aspect of the present application, a polycyclic compound prepared by the above method for preparing a polycyclic compound is proposed, wherein the prepared polycyclic compound comprises: a compound shown in formula I and a chlorine-containing organic matter, wherein the content of the compound shown in formula I is ≥99wt%, and the total content of the chlorine-containing organic matter is ≤300ppm. The characteristics and effects described for the above preparation of the polycyclic compound are also applicable to the polycyclic compound, and will not be repeated here.
[0047] In the fourth aspect of the present application, a use of the above-mentioned polycyclic compound and the above-mentioned method for preparing the polycyclic compound in the field of electrolyte and battery is proposed.
[0048] In a fifth aspect of the present application, an electrolyte is provided, comprising: an electrolyte additive, wherein the electrolyte additive comprises the above-mentioned polycyclic compound, or a polycyclic compound prepared by the above-mentioned method for preparing a polycyclic compound. The electrolyte is used in a battery to improve the electrochemical performance of the battery.
[0049] In some embodiments, based on the total mass of the electrolyte, the content of the electrolyte additive is 0.1-5 wt %.
[0050] In a sixth aspect of the present application, a battery is proposed, comprising: the above-mentioned electrolyte.
[0051] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0053] Figure 1 The present invention is a flow chart of preparing polycyclic compounds according to one embodiment of the present application.
[0054] Figure 2 This is the H NMR spectrum of the final product obtained according to Example 1 of the present application.
[0055] Figure 3 This is the NMR carbon spectrum of the final product obtained according to Example 1 of the present application. DETAILED DESCRIPTION
[0056] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.
[0057] In the first aspect of the present application, a polycyclic compound is provided, comprising: a compound represented by formula I and a chlorine-containing organic matter, wherein the content of the compound represented by formula I is ≥99wt% and the total content of the chlorine-containing organic matter is ≤300ppm based on the mass of the polycyclic compound.
[0058] ,
[0059] In formula I, R1 and R2 are independently any one of H, F, alkyl and fluoroalkyl.
[0060] It should be noted that R1 and R2 may be the same or different; the alkyl group and the fluoroalkyl group may be independently an alkyl group or a fluoroalkyl group having 1 to 10 carbon atoms, and may be an alkyl group or a fluoroalkyl group having 1 to 10 carbon atoms. In addition, the fluoroalkyl group may be an alkyl group partially or completely substituted with fluorine. Exemplarily, based on the mass of the polycyclic compound, the content of the compound shown in Formula I can be 99wt%, 99.2wt%, 99.4wt%, 99.5wt%, 99.7wt%, 99.9wt%, 99.92wt%, 99.95wt%, 99.97wt% or 99.99wt%, etc.; the total content of chlorine-containing organic matter can be ≤300ppm, ≤280ppm, ≤250ppm, ≤220ppm, ≤200ppm, ≤180ppm, ≤150ppm, ≤120ppm, ≤100ppm, ≤80ppm, ≤50ppm, ≤40ppm, ≤30ppm, ≤20ppm, ≤10ppm, ≤5ppm, and the like.
[0061] Among them, the compound shown in formula I can be used as an additive in the electrolyte to improve the electrochemical performance of the battery. Specifically, the compound shown in formula I is easy to form a dense CEI film at the positive electrode and a dense SEI film at the negative electrode during the battery formation stage. A small amount of inorganic salts (taking lithium batteries as an example, the inorganic salts include Li2SO4 and / or Li2O) will be formed in the CEI film formed by decomposition of the positive electrode, which improves the rigidity and flexibility of the positive electrode interface layer, inhibits the decomposition of the electrolyte, and improves the stability of the positive electrode interface film. In addition, the CEI film formed by the compound shown in formula I can also reduce the electrochemical impedance of the positive electrode and accelerate the active ions (such as Li + ) transmission rate, and at the same time help to form a more stable electrode-electrolyte interface, reduce the internal resistance and interface reaction of the battery, and play a role in protecting the positive electrode. In addition, it can also inhibit the dissolution of transition metal ions in the active material of the positive electrode plate, reduce the cycle capacity attenuation of the battery, and improve the cycle stability; lithium carbonate will be generated in the SEI film formed at the negative electrode, and lithium carbonate helps to improve the film formation uniformity and stability of the SEI film. In addition, the compound shown in Formula I is easy to obtain electrons and be reduced to cause the SO single bond to break, and the three O atoms in O, S=O and S=O on another cyclic sulfate group in the transition state formed after the break can form a claw-type space structure, which is easy to capture metal ions to form a cage complex, thereby stabilizing the already dissolved transition metal, reducing the catalytic decomposition side reaction of the transition metal on the SEI film, and inhibiting the negative impact caused by the deposition of the transition metal in the form of a single substance after the negative electrode is reduced; furthermore, the compound shown in Formula I has a low impedance, which is also beneficial to reducing the battery impedance.
[0062] The conventional synthesis process of the compound shown in Formula I inevitably contains impurities, and it is difficult to obtain a product with high purity and low impurity content. In particular, the existing synthesis method using sulfonyl chloride as a reaction raw material generally contains a large number of chlorine-containing organic impurities. The impurity components include but are not limited to chlorine-containing organics without cyclic sulfate groups and cyclic carbonate groups, chlorine-containing organics containing only cyclic carbonate groups, chlorine-containing organics containing only cyclic sulfate groups, chlorine-containing organics containing 1 to 2 cyclic carbonate groups and 1 cyclic sulfate group, etc. Such chlorine-containing organic impurities are prone to hydrolysis. When the polycyclic compound is introduced into the electrolyte as an additive, the free chlorine content in the electrolyte is easily increased, which in turn easily leads to corrosion of the positive electrode foil and dissolution of transition metal ions in the active material of the positive electrode sheet, reducing the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery.
[0063] In the present application, by using a polycyclic compound having a content of ≥99wt% of the compound shown in Formula I and a total content of chlorine-containing organic matter ≤300ppm as an additive in the electrolyte, the increase in the free chlorine content in the electrolyte caused by the introduction of the additive can be effectively reduced, thereby reducing the risk of corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet caused by the increase in the free chlorine content of the electrolyte. As a result, the problem of a decrease in the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery due to the presence of chlorine-containing organic impurities can be effectively improved, thereby improving the improvement effect of the polycyclic compound on the electrochemical performance of the battery.
[0064] In some specific embodiments of the present application, when at least one of R1 and R2 is not H, when synthesizing the compound shown in Formula I, an alcohol raw material containing corresponding substitution positions and substituent types can be obtained in advance, and then the alcohol raw material can be used to synthesize the compound shown in Formula I through processes such as ester exchange reaction and condensation reaction.
[0065] In some specific embodiments of the present application, R1 and R2 can be independently any one of H, F, and fluoromethyl, which is not only conducive to the synthesis of the compound shown in Formula I, but also can further avoid the introduction of chlorine-containing compounds in the additive, and reduce the free chlorine content that may be generated after the electrolyte additive is introduced into the electrolyte. When at least one of R1 and R2 is F, the end group of the hexavalent alcohol can be first fluorinated or fluoromethyl substituted, and the end group is more active and easier to replace, and then the hexavalent alcohol with fluorinated or fluoromethyl substituted end group is mixed with raw materials such as carbonate to carry out transesterification reaction, and subsequent condensation reaction and oxidation reaction.
[0066] In some specific embodiments of the present application, R1 and R2 may be independently H, that is, the compound represented by formula I may include: . The compound has a strong polarity, and its interaction with other non-polar molecules is weak, the friction and collision between molecules are small, and it has better stability than other sulfate compounds; in addition, compared with other sulfate compounds, the compound also has better thermal stability. It can not only be stored at room temperature without low-temperature storage, but also can operate stably in a wide voltage range. It has good cycle life and capacity retention rate, and also has better high-temperature performance. It can maintain relatively stable electrochemical performance under high temperature environment, thereby extending the service life of the battery. In addition, the oxidation and reduction potentials of the compound are both ahead of conventional electrolyte solvents. During the battery formation process, it will be oxidized at the positive electrode and reduced at the negative electrode before the solvent, and then it is easy to form a dense CEI film at the positive electrode and a dense SEI film at the negative electrode. Therefore, it is conducive to further improving the improvement effect of the polycyclic compound on the electrochemical performance of the battery.
[0067] In some specific embodiments of the present application, based on the mass of the polycyclic compound, the total content of chlorine-containing organic matter can be ≤100ppm, for example, ≤100ppm, ≤80ppm, ≤50ppm, ≤30ppm or 1-99ppm, etc. Meeting the given range can further reduce the increase in the free chlorine content in the electrolyte that may be caused by the introduction of the polycyclic compound, and thus can further reduce the risk of the electrolyte being prone to corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet due to the increase in the free chlorine content, thereby further improving the problem of the reduced effect of the compound shown in Formula I on the electrochemical performance of the battery due to the presence of impurities, and thus can improve the effect of the polycyclic compound on the electrochemical performance of the battery.
[0068] In some specific embodiments of the present application, based on the mass of the polycyclic compound, the content of the compound shown in Formula I can be 99-99.99wt%, for example, 99wt%, 99.1wt%, 99.5wt%, 99.8wt%, 99.9wt%, 99.95wt% or 99.99wt%, etc. In particular, when it is greater than 99.9wt%, the improvement effect of the polycyclic compound on the electrochemical performance of the battery can be further improved.
[0069] In some specific embodiments of the present application, chlorine-containing organic matter may include, but is not limited to, chlorine-containing organic matter without cyclic sulfate groups and cyclic carbonate groups, chlorine-containing organic matter containing only cyclic carbonate groups, chlorine-containing organic matter containing only cyclic sulfate groups, and chlorine-containing organic matter containing 1 to 2 cyclic carbonate groups and 1 cyclic sulfate group. Among them, in the synthesis process of the compound shown in Formula I, chlorine-containing organic matter may be produced due to excessive use of hexavalent alcohol, insufficient process conditions for transesterification and condensation reactions, etc. The several types of chlorine-containing organic impurities given are common impurities in the target product when the compound shown in Formula I is prepared using hexavalent alcohol, carbonate and thionyl chloride as raw materials. Reducing the content of the chlorine-containing organic matter is conducive to further improving the improvement effect of polycyclic compounds on the electrochemical performance of the battery.
[0070] In some specific embodiments of the present application, the chlorine-containing organic matter may include: , , For example, taking R1 and R2 as H, the chlorine-containing organic matter may include , , One or more of the above. The three chlorine-containing organic substances are common chlorine-containing organic impurities in the target product when the compound shown in Formula I is prepared using hexavalent alcohol, carbonate and thionyl chloride as raw materials. The above chlorine-containing organic substances are easily hydrolyzed to form free chlorine, which increases the risk of corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet. Reducing the content of the three chlorine-containing organic substances is conducive to further reducing the increase in the free chlorine content in the electrolyte that may be caused by the introduction of polycyclic compounds, reducing the risk of dissolution of transition metal ions in the positive electrode sheet, and improving the effect of polycyclic compounds on the electrochemical performance of the battery. Further, based on the mass of the polycyclic compound, , , The total content of can be ≤50ppm, for example, ≤45ppm, ≤40ppm, ≤35ppm, ≤30ppm, ≤20ppm, ≤10ppm or ≤5ppm, etc. This can further improve the problem of reduced improvement effect of the compound represented by formula I on the electrochemical performance of the battery due to chlorine-containing organic impurities.
[0071] In some specific embodiments of the present application, the polycyclic compound may further include other organic substances, and the other organic substances are selected from one or more of the following six compounds: , , , , , For example, taking R1 and R2 as H, the other organic matter can be one or more of the following 6 compounds: , , , , , . The several compounds given are also common impurities in the target product when the compound shown in Formula I is prepared using hexavalent alcohol, carbonate and thionyl chloride as raw materials. Reducing the total content of the impurities is conducive to further improving the improvement effect of polycyclic compounds on the electrochemical performance of the battery. Among them, based on the mass of the polycyclic compound, the total content of the 6 compounds can be ≤1000ppm, for example, ≤900ppm, ≤800ppm, ≤700ppm, ≤600ppm, ≤500ppm, ≤300ppm, ≤200ppm, ≤100ppm, ≤50ppm, ≤30ppm, and so on. Reducing the total content of impurities in the 6 compounds is conducive to further reducing the risk of a decrease in the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery due to the presence of impurities. Controlling the total content of impurities to meet the given range can further improve the improvement effect of polycyclic compounds on the electrochemical performance of the battery. Further, based on the mass of the polycyclic compound, the total content of the 6 compounds can be ≤200ppm.
[0072] At present, in the common synthesis process of the compound shown in Formula I, there are problems such as poor selectivity of the target product, low yield and more impurities of the target product, in addition, there are more solvent usage, cumbersome process, unfavorable for industrial production, and so on, therefore seek a kind of high conversion rate, high yield, and the reaction steps are relatively simple, and the method suitable for industrial production of polycyclic sulfates is imminent. Based on the same inventive concept as the first aspect of the present application, it is expected to obtain a polycyclic compound product with a chlorinated organic content of ≤300ppm, and a purity of the compound shown in Formula I of ≥99wt%, the present application proposes a method for preparing a polycyclic compound with a high conversion efficiency, high yield and low polycyclic compound containing chlorinated organic impurities.
[0073] In a second aspect of the present application, a method for preparing a polycyclic compound is provided, comprising:
[0074] (1) mixing a hexahydric alcohol, a monohydric alcohol, a carbonate and an alkaline catalyst, and conducting an ester exchange reaction at a temperature of 65 to 100° C. and under a pressure controlled to be less than 2.5 MPa for 0.5 to 6 hours to obtain compound 1;
[0075] (2) dissolving the compound 1 in a solvent and reacting the mixture with thionyl chloride to obtain a compound 2;
[0076] (3) reacting the compound 2 with an oxidant to obtain a compound represented by formula I,
[0077] Among them, the structural formulas of the hexahydric alcohol, the compound 1, and the compound 2 are respectively:
[0078] , , , R1 and R2 are independently any one of H, F, Cl, alkyl, and fluoroalkyl.
[0079] For example, Figure 1 Shows For hexavalent alcohol, It is a carbonate ester, with H3C-OH as a monohydric alcohol, and combined with thionyl chloride As raw materials to prepare the target product The flowchart also shows the intermediate products, target products and possible impurity components such as chlorine-containing organic matter and other organic compounds in the preparation process.
[0080] refer to Figure 1 It is understood that in step (1), the reaction activity of the hydroxyl groups at the terminal positions (1 and 6) of the hexamethylene alcohol is suppressed by using a monohydric alcohol and controlling the pressure to be less than 2.5 MPa, and then the reaction temperature is raised to 65-100°C, which is higher than the boiling point of the monohydric alcohol (methanol has the lowest boiling point in China, which is 65°C) by the action of pressure, so as to increase the reaction activity of the hydroxyl groups at the middle positions (2, 3, 4, and 5) of the hexamethylene alcohol, so that the activity of the hydroxyl groups at the middle positions of the hexamethylene alcohol is much higher than that of the terminal hydroxyl groups. At the same time, due to the heating and pressurizing conditions, compared with the hydroxyl groups at the 2 and 3 positions, the reaction activity of the hydroxyl groups at the middle positions of the hexamethylene alcohol is much higher than that of the terminal hydroxyl groups. The product generated by the reaction and the product generated by the reaction of the 4- and 5-hydroxyl groups, and the product generated by the reaction of the 3- and 4-hydroxyl groups (i.e., compound 1) have good symmetry and better stability. Therefore, under this condition, the selectivity for compound 1 and the conversion efficiency of compound 1 in the transesterification reaction can be improved, and an intermediate product having compound 1 can be obtained with high conversion rate and high selectivity. Compared with the conventional process for synthesizing the target product shown in formula I, which has low selectivity and easy generation of by-products, the process of step (1) of the present application can effectively reduce the residual hexavalent alcohol content in the transesterification reaction product, as well as the impurities. and The content of 2-hydroxy-2-nitropropene is 0.0447W, which is beneficial to further reduce the impurities that may exist in the condensation reaction product of step (2). , , , The formation of, and possible impurities produced in the subsequent oxidation reaction , The content.
[0081] In addition, in step (1), no additional organic solvent is used in the transesterification reaction, and carbonate and monohydric alcohol serve as both reactants and solvents, which is not only environmentally friendly but also easy to operate. It can effectively improve the problems of low reaction conversion rate, complicated reaction steps, high impurity generation, and inconvenience for industrial production in the synthesis of the compound represented by formula I.
[0082] In summary, the method for preparing a polycyclic compound of the above embodiment of the present application not only has high selectivity and high conversion rate for the compound shown in Formula I, but also has a low impurity content, which can effectively improve the low reaction conversion rate, complicated reaction steps, more impurities generated, and inconvenience for industrial production of the compound shown in Formula I during synthesis. The problem is also conducive to obtaining a target product with a chlorine-containing organic content of ≤300ppm and a purity of ≥99wt% of the compound shown in Formula I. The target product shown in Formula I obtained is used in an electrolyte to effectively reduce the increase in the free chlorine content in the electrolyte, thereby reducing the risk of corrosion of the positive electrode foil and dissolution of transition metal ions in the positive electrode sheet due to the increase in the free chlorine content of the electrolyte. Thus, the problem of a decrease in the improvement effect of the compound shown in Formula I on the electrochemical performance of the battery due to the presence of chlorine-containing organic impurities can be effectively improved, and the improvement effect of the obtained polycyclic compound on the electrochemical performance of the battery can be improved. It should be noted that the method for preparing polycyclic compounds in the second aspect of the present application and the polycyclic compounds in the first aspect of the present application are proposed based on the same inventive concept, and the characteristics and effects described for the polycyclic compounds in the first aspect of the present application are also applicable to the method for preparing polycyclic compounds in the second aspect of the present application, and will not be described one by one here.
[0083] Among them, reference Figure 1 It is understood that in step (1), the temperature of the transesterification reaction may be 65-100°C, for example, 65°C, 70°C, 80°C, 90°C or 100°C, etc., the pressure may be greater than atmospheric pressure but less than 2.5 MPa, for example, 0.2 MPa, 0.4 MPa, 0.6 MPa, 0.8 MPa, 1 MPa, 1.2 MPa, 1.4 MPa, 1.6 MPa, 1.8 MPa, 2 MPa, 2.2 MPa, 2.5 MPa, etc., and the time may be 0.5-6 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h, etc. Among them, if the pressure during the transesterification reaction is too low (for example, when it is negative pressure), a large amount of monohydric alcohol in the reaction system will be removed, which is not conducive to improving the selectivity of the transesterification reaction and inhibiting the impurities. The production of; however, the pressure during the transesterification reaction is too high. As the reaction proceeds, if the methanol content in the system is too high, the transesterification reaction is easily hindered, resulting in a lower conversion rate and an increase in residual raw materials. In the present application, by controlling the temperature, pressure and time of the transesterification reaction to meet the above ranges, a higher raw material conversion rate and a suitable transesterification reaction rate can be taken into account, thereby obtaining compound 1 with higher selectivity and yield and lower impurity content.
[0084] Further preferably, in step (1), the temperature of the transesterification reaction can be 70-90°C and the pressure can be 0.5-2.2 MPa. Further preferably, the temperature of the transesterification reaction can be 75-85°C and the pressure can be 1-2 MPa, which is beneficial to further take into account a higher raw material conversion rate and a suitable transesterification reaction rate, thereby obtaining compound 1 with higher selectivity and yield and lower impurity content.
[0085] In some specific embodiments of the present application, in step (1), after the ester exchange reaction is completed, it can also include: decompression treatment to remove low-boiling point components, which is beneficial to improve the purity of the compound shown in Formula I in the final product and reduce the impurity content. As some specific examples, the decompression treatment can be a decompression distillation treatment. Optionally, the pressure of the decompression treatment can be -90~-80kPa (i.e., 90~80kPa lower than the standard atmospheric pressure), for example, it can be -90kPa, -85kPa, -80kPa, etc., and the temperature of the decompression treatment can be 30~60℃, for example, it can be 35℃, 40℃, 45℃, 50℃, 55℃, etc., which is further beneficial to remove low-boiling point components.
[0086] In some specific embodiments of the present application, reference is made to Figure 1 It is understood that in step (1), the molar ratio of carbonate to hexavalent alcohol can be 3:1 to 5:1, such as 3 / 1, 3.5 / 1, 4 / 1, 4.5 / 1 or 5 / 1. Based on the amount of hexavalent alcohol, appropriately increasing the amount of carbonate is beneficial to accelerating the process of transesterification reaction, improving the conversion rate of raw materials, reducing the content of unreacted hexavalent alcohol in the intermediate product, and thus helping to reduce impurities in the final product. , In the present application, by controlling the amount of carbonate to meet the given range, the transesterification reaction can have a suitable reaction rate, which can improve the utilization rate of raw materials and the yield of compound 1 and reduce the impurities in the final product. , The content of carbonate can also reduce the excessively fast transesterification reaction when a large amount of carbonate is added, which causes the terminal hydroxyl groups of the hexyl alcohol to react and generate impurities. and The risk of subsequent impurities can be further reduced. , , The content.
[0087] In some specific embodiments of the present application, reference is made to Figure 1 It is understood that in step (1), the molar ratio of the monohydric alcohol to the hexhydric alcohol may be 10:1 to 20:1, for example, 10 / 1, 12 / 1, 14 / 1, 16 / 1, 18 / 1, 20 / 1, etc. Further preferably, the molar ratio of the monohydric alcohol to the hexhydric alcohol may be 12:1 to 18:1, and even more preferably, the molar ratio of the monohydric alcohol to the hexhydric alcohol may be 14:1 to 16:1. Controlling the relative amounts of the monohydric alcohol and the hexhydric alcohol to meet the above range can not only meet the demand for the monohydric alcohol to be used as a solvent to dissolve the reaction raw materials, but also reduce the risk of a large inhibitory effect on the ester exchange reaction when the amount of the monohydric alcohol is large, which is conducive to the smooth progress of the ester exchange reaction, and can also make the ester exchange reaction have a suitable reaction rate, reducing the risk that the terminal hydroxyl groups of the hexhydric alcohol will react to generate impurities due to the fact that the monohydric alcohol is not conducive to improving the selectivity of the ester exchange reaction when the amount is small. and , which can further reduce the impurities that may be formed later , , The content.
[0088] In some specific embodiments of the present application, in step (1), based on the mass of the hexavalent alcohol, the amount of the alkaline catalyst can be 0.01-5wt%, for example, 0.01wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc. Controlling the amount of the alkaline catalyst within the above range is not only conducive to the smooth progress of the transesterification reaction, but also reduces the risk of increasing the amount of thionyl chloride used in the subsequent condensation reaction due to excessive use of the alkaline catalyst, thereby generating more sulfur dioxide.
[0089] In some specific embodiments of the present application, in step (1), the amount of the alkaline catalyst can be 0.02-0.5wt% based on the mass of the hexavalent alcohol. More preferably, the amount of the alkaline catalyst can be 0.02-0.1wt% based on the mass of the hexavalent alcohol. In the present application, in order to facilitate industrialization, it is expected to simplify the post-processing process of each reaction step. In view of the use of an alkaline catalyst in the transesterification reaction in step (1), the system after the reaction is easily alkaline. If the neutralization or purification process is not performed, the alkaline catalyst will enter the condensation reaction process and consume the thionyl chloride in the second step, affecting the condensation reaction. However, if the alkaline catalyst is removed, the post-processing process of step (1) will be relatively complicated, for example, it is necessary to add an acidic substance such as oxalic acid to adjust the pH value, and then perform post-processing steps such as filtration and recrystallization. In the present application, by further reducing the amount of alkaline catalyst used, the post-treatment steps such as pH adjustment, filtration, and recrystallization after step (1) can be simplified. However, if the content of the catalyst is reduced, it is easy to affect the reaction rate, etc. The present application can make up for the defects caused by the reduction of the amount of catalyst by heating and pressurizing the treatment, thereby achieving the purpose of simplifying the post-treatment process. On this basis, by further adjusting the relative amounts of hexahydric alcohol, monohydric alcohol, and carbonate, as well as the reaction temperature and pressure conditions to meet the above ranges, the defects caused by the reduction of the amount of catalyst can be further made up, thereby achieving the purpose of simplifying the post-treatment process.
[0090] In some specific embodiments of the present application, in step (1), when the hexahydric alcohol When at least one of R1 and R2 is not H, when synthesizing the target product shown in formula I, a hexahydric alcohol raw material containing corresponding substitution positions and substituent types can be obtained in advance, and then the hexahydric alcohol raw material can be used to synthesize the compound shown in formula I through processes such as ester exchange reaction and condensation reaction.
[0091] In some specific embodiments of the present application, reference is made to Figure 1 It is understood that in step (1), the hexavalent alcohol may include but is not limited to one or more of mannitol, sorbitol, and galactitol. Selecting the given type of hexavalent alcohol can produce a compound with better stability. .
[0092] In some specific embodiments of the present application, in step (1), the carbonate may include, but is not limited to, one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and diphenyl carbonate.
[0093] In some specific embodiments of the present application, in step (1), the monohydric alcohol may include, but is not limited to, one or more of methanol, ethanol, propanol, isopropanol, butanol, and tert-butanol.
[0094] In some specific embodiments of the present application, in step (1), the alkaline catalyst may include, but is not limited to, one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, triethylamine, and pyridine.
[0095] In some specific embodiments of the present application, in step (2), after the condensation reaction is completed, it can also include: reflux deacidification treatment, thereby reducing the residual HCl produced by the condensation reaction, thereby reducing the free chlorine content that may be introduced into the electrolyte later. In some specific embodiments, the temperature of the reflux deacidification can be 40~80℃, for example, it can be 40℃, 50℃, 60℃, 70℃ or 80℃. In some specific embodiments, the temperature of the reflux deacidification can be 10~50min, for example, it can be 15min, 20min, 30min, 40min or 50min. Meeting the reflux deacidification treatment conditions is conducive to further reducing the residual HCl produced by the condensation reaction.
[0096] In some specific embodiments of the present application, reference is made to Figure 1 It is understood that in step (2), compound 1 can be dissolved in a solvent and then thionyl chloride can be added dropwise to carry out the condensation reaction. In this way, thionyl chloride is slowly added to the mixed solution to react with compound 1, which can significantly reduce the side reactions that may be caused by the relative excess of thionyl chloride, thereby better inhibiting the formation of impurities. Generation of.
[0097] In some specific embodiments of the present application, in step (2), the temperature of the condensation reaction may be 20-100°C, for example, 20-60°C, 20°C, 25°C, 30°C, 50°C, 60°C, 80°C or 100°C. Controlling the temperature of the condensation reaction to meet the given conditions is beneficial to reducing the increase in the reactivity of thionyl chloride caused by excessively high reaction temperature, resulting in the formation of chlorine-containing impurities (such as ) can also reduce the risk of increased reaction temperature, decreased reaction rate, increased reaction time, and decreased production efficiency, and can better balance the reaction efficiency and the purity of the final product.
[0098] In some specific embodiments of the present application, in step (2), the molar ratio of compound 1 to thionyl chloride can be 1: (2~3), for example, 1 / 2, 1 / 2.2, 1 / 2.5, 1 / 2.8, 1 / 3, etc., and the addition time of thionyl chloride can be 0.5~2h, for example, 0.5h, 0.8h, 1h, 1.5h or 2h, etc. By controlling the addition amount of thionyl chloride to meet the given range, it is not only conducive to reducing the risk of a decrease in the conversion rate of the hexavalent alcohol due to a relative shortage of thionyl chloride, but also the risk of the purity and yield of the target product of compound 2 and formula I being reduced due to the uncomplete reaction of hydroxyl groups, and also conducive to reducing the risk of an increase in chlorine-containing impurities when the amount of thionyl chloride is large. Further, by making the addition time of thionyl chloride meet the given range, a suitable thionyl chloride addition rate can be obtained, which can not only increase the reaction rate, but also reduce the risk of an increase in chlorine-containing impurities due to an excessively fast addition rate of thionyl chloride. Thus, the reaction rate can be taken into account, and the purity of compound 2 and the final product can be improved, and the impurity content can be reduced. The time of the condensation reaction is 1 to 4 hours, which is the time from the addition of thionyl chloride to the end of the condensation reaction. The time can be adaptively adjusted according to the addition time of thionyl chloride, so that the reaction continues for a period of time after the addition of thionyl chloride is completed, so that the condensation reaction is completely carried out.
[0099] In some specific embodiments of the present application, in step (2), the solvent may include, but is not limited to, one or more of ether solvents, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), tetrahydrofuran, and ester solvents.
[0100] In some specific embodiments of the present application, in step (3), the oxidant may be provided in the form of an aqueous solution, and after reacting compound 2 with the oxidant, the process may further include: heating the reaction product to remove moisture.
[0101] In some specific embodiments of the present application, in step (3), after the oxidation reaction is completed, the reaction product can be washed with water to remove inorganic salts. Specifically, the organic phase in the reaction product can be separated, and deionized water is added to extract and layer, and after repeated multiple times, the solvent is removed to obtain the compound shown in Formula I. In some specific embodiments, the removal of the solvent can be achieved by decompression treatment, wherein the pressure of the decompression treatment can be -90~-80kPa (i.e., 90~80kPa lower than the standard atmospheric pressure), for example, it can be -90kPa, -85kPa, -80kPa, etc., and the temperature of the decompression treatment can be 30~60°C, for example, it can be 35°C, 40°C, 45°C, 50°C, 55°C, etc., which is conducive to further removing the solvent component.
[0102] In some specific embodiments of the present application, in step (3), the specific type of the oxidant is not particularly limited, and those skilled in the art can flexibly select it according to actual needs. For example, the oxidant may include but is not limited to one or more of hydrogen peroxide, sodium hypochlorite, and sodium periodate. For example, the oxidant may be sodium hypochlorite. For another example, the oxidant may be hydrogen peroxide. The selection of hydrogen peroxide can not only further reduce the chlorine-containing impurities that may be introduced into the final product, but also the generated moisture can be removed by heating treatment.
[0103] In some specific embodiments of the present application, in step (3), the oxidant may include sodium hypochlorite and / or sodium periodate, and the molar ratio of compound 2 to the oxidant may be 1:(2-2.5), for example, 1 / 2, 1 / 2.1, 1 / 2.2, 1 / 2.3, 1 / 2.4 or 1 / 2.5, etc. Controlling the content of the oxidant to meet the given range is conducive to fully oxidizing compound 2, improving the yield and purity of the target product shown in formula I, and can also reduce the chlorine-containing impurities and / or inorganic salt impurities that may be introduced when the amount of the oxidant is large.
[0104] In some specific embodiments of the present application, in step (3), the oxidant may include sodium hypochlorite and / or sodium periodate, and the oxidant may be provided in the form of an aqueous solution. Before the reaction between compound 2 and the oxidant, the condensation reaction product is first dissolved in a non-aqueous solvent, and then the oxidant is added to carry out an oxidation reaction. After the oxidation reaction, the following steps are further performed: (4-1) heating the reaction product to remove moisture; (4-2) after the moisture is removed, inorganic salts are precipitated, and the inorganic salts are removed by filtration. In this way, moisture and inorganic salts in the final product can be removed, such as reducing the content of sodium hypochlorite or sodium periodate to dozens or even several ppm, while also avoiding the loss of the target product in the water washing process.
[0105] In the third aspect of the present application, a polycyclic compound prepared by the above method for preparing a polycyclic compound is proposed, wherein the prepared polycyclic compound comprises: a compound shown in formula I and a chlorine-containing organic matter, wherein the content of the compound shown in formula I is ≥99wt%, and the total content of the chlorine-containing organic matter is ≤300ppm. The characteristics and effects described for the above preparation of the polycyclic compound are also applicable to the polycyclic compound, and will not be repeated here.
[0106] In the fourth aspect of the present application, a use of the polycyclic compound and the method for preparing the polycyclic compound in the field of electrolyte and battery is proposed. The features and effects described for the polycyclic compound and the method for preparing the polycyclic compound are also applicable to this use, and will not be described in detail here.
[0107] In the fifth aspect of the present application, an electrolyte is proposed, comprising: an electrolyte additive, wherein the electrolyte additive comprises the above-mentioned polycyclic compound, or a polycyclic compound prepared by the above-mentioned method for preparing a polycyclic compound. It should be noted that the characteristics and effects described for the above-mentioned polycyclic compound and the above-mentioned method for preparing a polycyclic compound are also applicable to the electrolyte, and are not described one by one here. In general, the use of the electrolyte in a battery can better improve the electrochemical performance of the battery.
[0108] Typically, the electrolyte also includes an electrolyte salt and an organic solvent. Optionally, the electrolyte can be used in a lithium battery. Taking a lithium battery as an example, the electrolyte salt can be a lithium salt. Among them, the organic solvent is the main component of the electrolyte and is an important carrier for ion transmission. It can make the organic solvent have a higher solubility of lithium salt, so that the electrolyte has a higher ionic conductivity. After the lithium salt is dissolved in the organic solvent, lithium ions can be released. The lithium ions and the organic solvent form a solvation structure, which is conducive to the rapid migration of lithium ions.
[0109] In some specific embodiments of the present application, based on the total mass of the electrolyte, the content of the electrolyte additive can be 0.1~5wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, etc., so that the electrolyte can be used in the battery to achieve a good improvement in the electrochemical performance of the battery.
[0110] In some specific embodiments of the present application, the organic solvent may include a carbonate solvent and / or a carboxylate solvent, thereby improving the dispersion uniformity and ion conductivity of the electrolyte.
[0111] In some specific embodiments of the present application, the organic solvent may include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate. The organic solvent in the given range can make the electrolyte have a higher ionic conductivity after dissolving the lithium salt, which is conducive to further improving the electrochemical performance of the battery.
[0112] In some specific embodiments of the present application, the composition of the organic solvent can be flexibly adjusted according to the actual situation of the battery system, for example, as some specific examples, the organic solvent can include ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a mass ratio of 1: (0.5-2): (0.5-2). The organic solvent can be suitable for a layered transition metal oxidant as a positive electrode active material (for example, a chemical formula of Li a Nib Co c M1 d M2 e O f R g A battery system comprising a positive electrode active material, wherein 1≤a≤1.2, 0.6≤b≤1, 0≤c≤1, 0≤d≤1, 0≤e≤0.2, b+c+d+e=1, 1≤f≤2, 0≤g≤1, f+g=2; M1 includes Mn and / or Al, M2 includes at least one of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, and Nb, and R includes at least one of N, F, S, and Cl).
[0113] In some specific embodiments of the present application, the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4) and lithium bis(trifluoromethanesulfonyl)imide (C2F6LiNO4S2).
[0114] In some specific embodiments of the present application, the molar concentration of the lithium salt in the electrolyte may be 0.8 mol / L to 2 mol / L, for example, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L or 2 mol / L, etc. The cost of lithium salt in the electrolyte accounts for a relatively high proportion, and controlling the concentration of lithium salt in the electrolyte to meet the given range is beneficial for fully dissolving the lithium salt in the organic solvent, and also for making the electrolyte have both high ionic conductivity and low manufacturing cost.
[0115] In some specific embodiments of the present application, in addition to the above components, the electrolyte may optionally include a small amount of other conventional additives or auxiliary agents that can improve certain battery properties. Those skilled in the art can choose according to actual needs, which will not be described in detail here.
[0116] In the sixth aspect of the present application, a battery is proposed, comprising: the above-mentioned electrolyte. It should be noted that the characteristics and effects described for the above-mentioned electrolyte in this application are also applicable to the battery, and will not be repeated here. In general, the battery has good electrochemical properties. In addition, it should be noted that the type of the battery is not particularly limited, and those skilled in the art can flexibly choose according to actual needs, for example, it can be a secondary battery.
[0117] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0118] In some embodiments of the present application, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, the positive electrode current collector may include a metal foil or a composite positive electrode current collector, for example, the metal foil may be aluminum foil, the composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the surface of the polymer material base, for example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.). The positive electrode active material may include the above-mentioned positive electrode active material or a commonly used positive electrode active material in the art. The conductive agent and the binder may be conventional materials in the art.
[0119] In some embodiments of the present application, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil or a composite current collector, for example, the metal foil may be a copper foil, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate, for example, the composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.). The negative electrode active material may include a commonly used negative electrode active material in the art (such as at least one of commonly used negative electrode active materials such as graphite, silicon-carbon composite materials, silicon materials, lithium metal, lithium titanate, etc.). The conductive agent and the binder may be conventional materials in the art.
[0120] In some embodiments of the present application, the isolation membrane can adopt an isolation membrane that is well known in the art and can be used in batteries and is stable to the electrolyte used. For example, its material can include but is not limited to at least one of polyolefins, aromatic polyamides, polytetrafluoroethylene, and polyether sulfone, such as a polyethylene diaphragm, a polypropylene diaphragm, a PE ceramic coated diaphragm, etc., and the specific material can be flexibly selected according to needs.
[0121] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0122] Example 1
[0123] 1. Preparation of polycyclic compounds:
[0124] (i) Mannitol, dimethyl carbonate, methanol and sodium hydroxide were added to a reaction kettle, and the reaction was carried out at 1 MPa and 75°C for 1 h. Low-boiling materials were removed by decompression at (-85±5) kPa and 50°C to obtain a dry product mainly composed of compound 1. The structural formula of compound 1 is , in this embodiment, ;
[0125] (ii) dissolving the dried product in dichloromethane (the mass ratio of dichloromethane to the dried product is 5:2), and adding thionyl chloride dropwise to the dried product solution at room temperature for 1.5 hours, stirring for 3 hours, and the dried product The molar ratio of thionyl chloride to thionyl chloride is 1:2.1; reflux and deacidify at 40°C for 30 minutes to obtain a reaction product, which includes compound 2. The structural formula of compound 2 is , in this embodiment, ;
[0126] (iii) adding a 12% sodium hypochlorite aqueous solution to the reaction product of step (2) to carry out an oxidation reaction, separating the layers, taking the organic phase, washing with deionized water, extracting and separating the layers, repeating this process three times, and removing the solvent under reduced pressure at (-85±5) kPa and 30° C. to obtain a final product represented by formula I , in this embodiment, The molar ratio of sodium hypochlorite to compound 2 is 2:1.
[0127] 2. Preparation of positive electrode
[0128] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3O2 positive electrode material (NCM523), conductive agent SuperP (conductive carbon black) and binder polyvinylidene fluoride (PVDF) are mixed evenly according to the weight ratio of 96.8:2:1.2, and N-methylpyrrolidone (NMP) is added. Stir under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the coating amount is 33g / m 2 After drying at 85°C, cold pressing is performed, and trimming, cutting, and slitting are performed. After slitting, it is dried at 85°C under vacuum conditions for 4 hours, and the pole ears are welded to obtain the positive electrode sheet.
[0129] 3. Preparation of negative electrode sheet
[0130] The negative electrode active material graphite, the conductive agent Super P (conductive carbon black), the thickener CMC (sodium carboxymethyl cellulose), and the binder styrene-butadiene rubber were mixed in a weight ratio of 95:1.5:1.5:2, and deionized water was added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the coating amount was 20.1 g / m 2 After drying at 85°C, cold pressing is performed, and edge trimming, cutting, and striping are performed. After stripping, it is dried at 85°C for hours under vacuum conditions, and the tabs are welded to obtain the negative electrode sheet.
[0131] 4. Preparation of electrolyte
[0132] In a glove box filled with argon (water <10ppm, oxygen <1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were used as organic solvents in a mass ratio of EC:EMC=3:7, lithium hexafluorophosphate (LiPF6) 12.5% was used as lithium salt, vinyl sulfate (DTD) was used as a conventional additive, and the final product obtained in step 1 was used as an electrolyte additive. The lithium salt concentration was configured to be 1 mol / L, and the mass proportion of the electrolyte additive in the electrolyte was 3wt% of the electrolyte.
[0133] 5. Preparation of isolation film
[0134] A polyethylene isolation film with a thickness of 8 μm was selected.
[0135] 6. Lithium-ion battery preparation
[0136] The prepared positive electrode sheet, negative electrode sheet and isolation film are stacked in order, the isolation film is placed between the positive electrode sheet and the negative electrode sheet, and then rolled and flattened and put into an aluminum foil packaging bag, which is vacuum-baked at 75°C for 48 hours to obtain a battery cell, and the above-mentioned electrolyte is injected into the battery cell in a glove box, and the preparation of the lithium-ion battery is completed after packaging, formation, aging and capacity separation.
[0137] Examples 2 to 15 and Comparative Examples 1 to 6
[0138] The differences between Examples 2 to 15 and Comparative Examples 1 to 6 and Example 1 are detailed in Tables 1 to 4 (wherein Tables 1 and 2 show some of the differences between Examples 1 to 15 and Comparative Examples 1 to 5, and Tables 3 and 4 show some of the differences and test results between Examples 1 to 15 and Comparative Examples 1 to 6).
[0139] The structure, purity, content of chlorine-containing organic impurities, and battery cycle performance of the polycyclic compounds obtained in Examples 1 to 15 and Comparative Examples 1 to 6 were tested. The test method is as follows, and the test results are shown in Tables 3 to 4. Figure 2 and Figure 3 shown.
[0140] (1) Perform NMR testing on the final product of the polycyclic compound using a nuclear magnetic resonance (NMR) spectrometer to determine the compound structure of the final product; perform liquid chromatography testing on the final product of the polycyclic compound using a high performance liquid chromatograph to quantitatively analyze the components of the final product; and perform content analysis of chlorine-containing organic matter using high performance liquid chromatography.
[0141] (2) Cycle performance test: The formed battery was charged to 4.2V at room temperature using a constant current and constant voltage of 1C, charged to a cut-off current of 0.05C at a constant voltage of 4.2V, and discharged to 2.75V at 1C, and the initial discharge capacity of the battery was measured; 1000 charge and discharge cycles were performed, and the discharge capacity of the battery after 500 charge and discharge cycles was measured. The cycle capacity retention rate was calculated based on the cycle capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0142] (3) High temperature storage test: at 25 o C is charged to 4.2V at 1.0C constant current, charged to a cut-off current of 0.05C at 4.2V constant voltage, and then discharged to 2.75V at 1.0C constant current. The discharge capacity is recorded as C1. o C, charge at 1.0C constant current to 4.2V, charge at 4.2V constant voltage to a cut-off current of 0.05C, and then transfer the battery to 60 o C for 30 days, and then discharge the battery to 2.75V at a constant current of 1.0C. The discharge capacity is recorded as C2. o C storage 30 days capacity retention rate = C2 / C1*100%.
[0143]
[0144] Results and Conclusions:
[0145] Combining Examples 1 to 15 and Comparative Examples 1 to 6 and Tables 1 and 2, it can be seen that the final product obtained by the method of the above embodiment of the present invention has a higher purity, and the total content of chlorine-containing organic impurities is less, generally below 300 ppm. Taking Example 1 as an example, Figure 2 and Figure 3 The nuclear magnetic hydrogen spectrum and carbon spectrum of the final product obtained in Example 1 are shown, and its structural formula is shown in Table 2, with high purity and a total content of chlorine-containing organic impurities of 67ppm. In addition, in combination with Examples 1 to 4 and Comparative Examples 1, 2, 4, and 5, it can be seen that under the same conditions, the transesterification reaction is carried out under specific heating and pressurization conditions, and the selectivity and yield of the target product can also be improved, and appropriately increasing the pressure is also conducive to further improving the selectivity and yield of the target product. In combination with Example 1 and Comparative Example 3, it can be seen that under the same conditions, the use of monohydric alcohol has a great effect on improving the yield, purity and reducing the content of chlorine-containing organic matter. Further, in combination with Examples 1 to 15 and Comparative Examples 1 to 6, it can be seen that the final product (i.e., a polycyclic compound) with a purity of not less than 99% and a content of organic chlorine below 300ppm obtained in the above embodiment is used as an electrolyte additive in the electrolyte, which is also conducive to further improving the electrochemical performance of the battery.
[0146] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0147] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A polycyclic compound product, characterized in that: include: The compound represented by formula I and the chlorine-containing organic matter, based on the mass of the polycyclic compound product, the content of the compound represented by formula I is ≥99wt%, and the total content of the chlorine-containing organic matter is 5 to 300ppm, The chlorine-containing organic matter includes: In the compound represented by formula I and the chlorine-containing organic compound, R1 and R2 are independently any one of H, F, alkyl and fluoroalkyl.
2. The polycyclic compound product according to claim 1, characterized in that: At least one of the following conditions is met: (a) R1 and R2 are independently any one of H, F, and fluoromethyl; (b) based on the mass of the polycyclic compound product, the total content of the chlorine-containing organic matter is 5 to 100 ppm; (c) Based on the mass of the polycyclic compound product, the content of the compound represented by Formula I is greater than 99.9 wt %.
3. The polycyclic compound product according to claim 1 or 2, characterized in that: At least one of the following conditions is met: (i) The chlorine-containing organic matter includes: Wherein, R1 and R2 are independently any one of H, F, alkyl and fluoroalkyl; (ii) the compound represented by formula I includes:
4. The polycyclic compound product according to claim 3, characterized in that: Based on the quality of the polycyclic compound product, The total content is 5 to 50 ppm.
5. A method for preparing a polycyclic compound, characterized in that: include: (1) mixing a hexahydric alcohol, a monohydric alcohol, a carbonate and a basic catalyst, and conducting an ester exchange reaction at a temperature of 65 to 100° C. and a pressure of 0.2 to 2.5 MPa for 0.5 to 6 hours to obtain compound 1; (2) dissolving the compound 1 in a solvent and reacting the mixture with thionyl chloride to obtain a compound 2; (3) reacting the compound 2 with an oxidant to obtain a compound represented by formula I, Wherein, the structural formulas of the hexahydric alcohol, the compound 1, the compound 2 and the compound represented by formula I are: R1 and R2 are each independently any one of H, F, alkyl and fluoroalkyl.
6. The method according to claim 5, characterized in that Step (1) satisfies at least one of the following conditions: (A) After the transesterification reaction is completed, the following steps are further included: reducing pressure to remove low boiling point components; (B) the temperature of the transesterification reaction is 70 to 90° C., the pressure is 0.5 to 2.2 MPa, and the time is 0.5 to 6 hours; (C) the molar ratio of the carbonate to the hexahydric alcohol is 3:1 to 5:1; (D) the molar ratio of the monohydric alcohol to the hexahydric alcohol is 10:1 to 20:1; (E) Based on the mass of the hexahydric alcohol, the amount of the alkaline catalyst is 0.01 to 5 wt %; (F) the hexavalent alcohol includes one or more of mannitol, sorbitol, and galactitol; (G) the carbonate comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and diphenyl carbonate; (H) the monohydric alcohol includes one or more of methanol, ethanol, propanol, and butanol; (I) The alkaline catalyst includes one or more of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium tert-butoxide, triethylamine, and pyridine.
7. The method according to claim 5 or 6, characterized in that: At least one of the following conditions is met: (I) In step (2), after the condensation reaction is completed, the step further comprises: reflux deacidification treatment; (II) In step (2), compound 1 is dissolved in a solvent, and then thionyl chloride is added dropwise to carry out the condensation reaction; (III) In step (2), the condensation reaction temperature is 20 to 100° C. and the time is 1 to 4 hours; (IV) In step (2), the molar ratio of the compound 1 to the thionyl chloride is 1:(2-3), and the addition time of the thionyl chloride is 0.5-2h; (V) In step (2), the solvent comprises one or more of an ether solvent, N,N-dimethylformamide, N,N-dimethylacetamide, and an ester solvent; (VI) In step (3), the oxidant is provided in the form of an aqueous solution, and after reacting the compound 2 with the oxidant, the method further comprises: heating the reaction product to remove moisture.
8. The method according to claim 7, characterized in that In step (2), after the condensation reaction is completed, the method further comprises: reflux deacidification treatment, the temperature of the reflux deacidification treatment is 40 to 80° C., and / or the time of the reflux deacidification treatment is 10 to 50 minutes.
9. The method according to claim 8, characterized in that Step (1) satisfies at least one of the following conditions: (①) The temperature of the transesterification reaction is 75-85°C and the pressure is 1-2Mpa; (②) the molar ratio of the monohydric alcohol to the hexahydric alcohol is 12:1 to 18:1; (③) Based on the mass of the hexavalent alcohol, the amount of the alkaline catalyst is 0.02 to 0.5 wt %.
10. The method according to claim 9, characterized in that Step (1) satisfies at least one of the following conditions: (α) the molar ratio of the monohydric alcohol to the hexahydric alcohol is 14:1 to 16:1; (β) Based on the mass of the hexavalent alcohol, the amount of the alkaline catalyst is 0.02 to 0.1 wt %.
11. A polycyclic compound product prepared by the method according to any one of claims 5 to 10, characterized in that: include: The compound represented by formula I and chlorine-containing organic matter, the content of the compound represented by formula I is ≥99wt%, the total content of the chlorine-containing organic matter is 5-300ppm, and the chlorine-containing organic matter includes: Wherein, R1 and R2 are each independently any one of H, F, alkyl and fluoroalkyl.
12. Use of the polycyclic compound product according to any one of claims 1 to 4 or the polycyclic compound product prepared by the method according to any one of claims 5 to 10 in the field of electrolytes and batteries.
13. An electrolyte, characterized in that: include: An electrolyte additive, wherein the electrolyte additive comprises the polycyclic compound product according to any one of claims 1 to 4, or the polycyclic compound product prepared by the method according to any one of claims 5 to 10.
14. The electrolyte according to claim 13, characterized in that Based on the total mass of the electrolyte, the content of the electrolyte additive is 0.1-5wt%.
15. A battery, characterized in that: include: The electrolyte according to claim 13 or 14.
Citation Information
Patent Citations
Lithium ion battery electrolyte additive cyclic ethylene carbonate sulfate and preparation method thereof
CN111755753A
Electrolyte additive, electrolyte and battery
CN118040058A
Polyol carbonate bisulfate compound and preparation method thereof
CN118184644A
CN15207440A